Bordadoras de sueños e industria turística en Quintana Roo, México - Salinas Urquieta, María Eugenia (Oltreoceano - Rivista sulle migrazioni, 2021)
El ensayo aborda el significado de la indumentaria para las bordadoras mayas de hipiles en Quintana Roo: signo de pertenencia étnica y orgullo ancestral, manifestación de malestar por la discriminación y racismo de las mujeres mayas en contextos urbanos. Handicrafts and Artisans in the global world, paradoxes, transactions, market and cultural resistance in tourism context. The case of Quintana Roo, Mexico In this analysis will be talked Quintana Roo Mayan women weavers as a sign of their ethnic belonging and ancestral pride. In addition, it will be discussed at the same time the marketing and expropriation of their products. In the same way, it will be talked about the racism and discrimination that Mayan women suffer in the urban contexts. Ricamatrici di sogni e l’industria del turismo a Quintana Roo, Messico Il saggio affronta il significato degli indumenti per le ricamatrici mayas de hipiles a Quintana Roo: segno di appartenenza etnica e d’orgollo ancestrale, manifestazione di disagio per la discriminazione e per il razzismo di cui sono vittime le donne mayas nei contesti urbani.